Dietary administration of silk microparticles improves the epidermal and dermal regeneration after a skin wounding in gilthead seabream (Sparus aurata L.). Issue 124 (May 2022) - Albaladejo-Riad, Nora; Espinosa Ruiz, Cristóbal; Esteban, M. Ángeles
Abstract: The impact of dietary supplementation with silk fibroin (SF) microparticles on the wound healing process in gilthead seabream ( Sparus aurata ) skin was studied. A control diet was enriched with different SF levels: 0 (control), 50 (SF50 diet), and 100 (SF100 diet) mg Kg − 1 to form three experimental diets and was fed to seabream for 30 days. Experimental wounds were performed and after 7 days post-wounding (dpw) skin mucus immunity, macroscopic wound closure, and skin regeneration were studied at a microscopic and genetic level. Results indicated that fish fed SF100 did not suffer the decreases in protease and IgM levels observed in the skin mucus of wounded fish fed with the control diet. Macroscopic findings illustrated that dietary SF100 significantly improved the wound closure ratio compared to those reared in the control group. At a microscopic level, changes in the shape of keratocyte cells were evident in the wounded fish. In addition, the intercellular spaces present between epidermal cells and their proliferation in the epidermis, as well as the presence of blood vessels in the dermis were significantly statistically higher in the skin of fish fed the SF100 diet and sampled at 7 dpw compared to those observed in the skin of fish fed the control or SF50 diets. Moreover, regarding the RNA: DNA ratio, statistically significant increases and decreases were observed in fish fed the control and SF100 diet, respectively, in non-wounded and wounded fish. Interestingly, dietary SF100 supplementation improved skin cell proliferation, enhanced the inflammatory phase, and increased the expression of important genes involved in tissue repair and extracellular matrix formation. In conclusion, the SF100 diet can be considered as an appropriate feed additive to improve wound healing in gilthead seabream. Graphical abstract: Image 1 Highlights: The impacts of dietary supplementation with silk fibroin microparticles (SF) on the skin wound healing process were studied. The macroscopic wound closure and the skin regeneration at a microscopic and genetic level were studied. At microscopic levels, changes in the keratocyte cells shape were evident in wounded fish. Dietary SF100 supplementation improved the skin cell proliferation and enhanced the inflammatory phase.